2022
DOI: 10.1037/scp0000250
|View full text |Cite
|
Sign up to set email alerts
|

Locating the sacred within the therapeutic landscape: Influence of therapists’ religious and spiritual beliefs on psychotherapeutic practice.

Abstract: Religious and spiritual beliefs constitute individual identities and are central to personal world-views. Religion and spirituality of clients and therapists’ enter into the therapy process in multiple ways, and the need to understand their role, particularly in religiously diverse contexts cannot be underscored enough. This article explores the religious and spiritual beliefs and practices of psychotherapists from India, and how they impact their psychotherapeutic practice. An exploratory qualitative study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Koenig (2013) specifically called upon counselors to be mindful of their religious beliefs in client care, although existing studies have rarely examined how counselors' religious beliefs, when involved in the counselors' decision-making, influenced their treatment objectives. A recent study by Duggal and Sriram (2021) has shown that therapists' religious beliefs were interwoven with choices of therapeutic techniques and theoretical orientation. Our finding that participants who reported that religion played a less important role in their lives more strongly endorsed treatment objectives related to firearm storage in a home with young children suggests that counselors' treatment objectives are indeed influenced, at least to some extent, by religion.…”
Section: Discussionmentioning
confidence: 99%
“…Koenig (2013) specifically called upon counselors to be mindful of their religious beliefs in client care, although existing studies have rarely examined how counselors' religious beliefs, when involved in the counselors' decision-making, influenced their treatment objectives. A recent study by Duggal and Sriram (2021) has shown that therapists' religious beliefs were interwoven with choices of therapeutic techniques and theoretical orientation. Our finding that participants who reported that religion played a less important role in their lives more strongly endorsed treatment objectives related to firearm storage in a home with young children suggests that counselors' treatment objectives are indeed influenced, at least to some extent, by religion.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual beliefs and practices have been seen to promote therapist resilience and self-care (Duggal & Sriram, 2021). Furthermore, incorporating spirituality into treatment of trauma survivors is very significant because survivors often enter therapy struggling with global spiritual meaning systems that cannot accommodate their experiences of trauma.…”
Section: Research and Postsecular Spiritually Integrated Gestalt Therapymentioning
confidence: 99%